A Phase I Clinical Trial of the Phosphatidylserine-targeting Antibody Bavituximab in Combination With Radiation Therapy and Capecitabine in the Preoperative Treatment of Rectal Adenocarcinoma. (October 2018) - Meyer, Jeffrey; Arriaga, Yull; Anandam, Joselin; Karri, Sirisha; Syed, Samira; Verma, Udit; Abdelnaby, Abier; Raja, Grace; Dong, Ying; Beg, Muhammad Shaalan; Balch, Glen
Abstract : Objectives: There is interest in improving the tumoricidal effects of preoperative radiotherapy for rectal carcinoma by studying new radiosensitizers. The safety and toxicity profile of these combination regimens needs rigorous clinical evaluation. The primary objective of this study was to evaluate the toxicity of combining bavituximab, an antibody that targets exposed phosphatidylserine, with capecitabine and radiation therapy. Materials and Methods: Patients with stage II or III rectal adenocarcinoma were enrolled on a phase I study combining radiation therapy, capecitabine, and bavituximab. A standard 3+3 trial designed was used. Results: In general, bavituximab was safe and well tolerated in combination with radiation therapy and capecitabine in the treatment of rectal adenocarcinoma. One patient at the highest dose level experienced a grade III infusion reaction related to the bavituximab. One tumor demonstrated a complete pathologic response to the combination treatment. Conclusions: Bavituximab is safe in combination with capecitabine and radiation therapy at the doses selected for the study. Further clinical investigation would be necessary to better define the efficacy of this combination.